Subsídios para elaboração e utilização de material didático de língua estrangeira para a terceira idade - Scopinho, Raquel Albano (2009)
Through the investigation of the English teaching/learning process in two third age universities and through the presentation of the profile of these age group learners, we aim to provide contributions for further developing materials for foreign language teaching which are focused on the referred age group. Bearing in mind that this issue demands knowledge not only of the teaching/learning process, but also the aspects related to the alterations which occur during the ageing process, the theoretical support of this research relies on the Applied Linguistics and Gerontology knowledge. The analyzed data show some aspects to be considered during the development and use of such classroom materials. These aspects are: the loss of visual and hearing acuity, the memory ability of these learners and beliefs related to this subject, the question of the elderly language, the presence of yesterday in their speech, among other factors which are related to ageing process. Besides these aspects, we stress the benefits of a social and cognitively motivating environment for the development and maintenance of the elderly physical and mental abilities. Another fact to be considered is the necessity of overcoming possible stereotyped or prejudiced ideas, or even images of the elderly and the old age which are currently used in society, mainly when it refers to the process of knowledge acquisition and to the foreign language teaching/learning process. This research results in proposals to the use and development of didactic materials for foreign language to the third age students.